Increasing skin cancer incidence in young, affluent, urban populations: a challenge for prevention. (2nd August 2014) - Deady, S.; Sharp, L.; Comber, H.
Summary Background Nonmelanoma skin cancer (NMSC) is the most common cancer in white people, but is registered inconsistently by population‐based registries. Objectives To analyse the changing profile of NMSC in a national population, to interpret evolving patterns of sun exposure and to recommend measures to reduce risk. Methods We analysed trends in the demographic, clinical and socioeconomic profile of > 50 000 cases of NMSC registered between 1994 and 2011 by the Irish National Cancer Registry, which aims to register all episodes of NMSC in the Irish population to a high degree of completeness. Results The incidence of cutaneous basal cell (BCC) and squamous cell carcinoma (SCC) was stable from 1994 to 2002, but increased significantly (BCC more than SCC) in the subsequent decade. The largest relative increases in the incidence of BCC were in younger populations and in clothed body sites. The incidence of both cancers was lower in rural areas. Incidence of BCC and, to a lesser extent, of SCC, increased with increasing affluence in urban, but not in rural, areas. Conclusions Recent increases in skin cancers on the trunk and limbs in younger people appear to be related to increasing affluence and consequent leisure‐related, episodic sun exposure. This population is at high risk of subsequent skin cancers throughout life and will need active surveillance. As preventive programmes are cost‐effective in lowering the incidence of NMSC, they should be targeted at leisure exposure in young people. The recording of consistent international data on NMSC should also be a priority.